Liquid metal slurry and preparation method and application thereof

Through cellulose nanocrystal stabilizer and Pickering emulsion technology, the surface tension and compatibility problems of gallium-based liquid metal were solved, and a high-stability liquid metal paste and Janus film suitable for flexible electrons were prepared, realizing the Application potential in the field of flexible electronics.

CN119252527APending Publication Date: 2025-01-03SOUTH CHINA NORMAL UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411401370.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Gallium-based liquid metals are difficult to pattern the matrix due to their huge surface tension and poor compatibility with the matrix, and commonly used surfactants such as thiols have irritating odors and poor biocompatibility, which is limited. Its application.

Method used

Using cellulose nanocrystals as stabilizers, gallium-based liquid metal slurry is prepared through Pickering emulsion technology to form stable liquid metal microspheres. Combined with sonication and centrifugal purification technology, good stability and biocompatibility are prepared. Alloy ink and Janus film.

Benefits of technology

The high stability and good dispersion of liquid metal paste are achieved, the alloy ink is easily patterned on the substrate, and the Janus film has an asymmetric structure and good Joule thermal performance and photothermal conversion performance, which is suitable for the field of flexible electronics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005075364230000011
    Figure HDA0005075364230000011
  • Figure HDA0005075364230000012
    Figure HDA0005075364230000012
  • Figure HDA0005075364230000021
    Figure HDA0005075364230000021
Patent Text Reader

Abstract

The invention relates to the technical field of flexible electronics, and discloses liquid metal slurry and a preparation method and application thereof. The liquid metal slurry comprises a liquid metal Pickering emulsion; the liquid metal Pickering emulsion comprises liquid metal and a stabilizer; the liquid metal comprises gallium-based liquid metal; the stabilizer comprises cellulose nanocrystals. The liquid metal slurry provided by the invention does not have obvious sedimentation and agglomeration phenomena after standing for 24 hours, is good in stability and has the characteristics of Pickering emulsion, and emulsion microspheres in the liquid metal slurry are micron-sized, uniform in sphere and good in dispersity; the alloy ink obtained by centrifugally purifying the liquid metal slurry can be easily patterned on the substrate, has good adhesiveness with the substrate and low ink mark resistance, and has the potential of being applied to flexible electronics; in the Janus membrane provided by the invention, the compatibility of the liquid metal and the polymer matrix is relatively good, and the Joule thermal performance, the photothermal conversion performance, the softness and the elasticity of the membrane are relatively good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of flexible electronic technology, and in particular to a liquid metal slurry and a preparation method and application thereof. Background Art

[0002] Gallium-based liquid metal has the characteristics of good fluidity, good electrical conductivity, high conductivity, low saturated vapor pressure, good biocompatibility, etc., and has good application prospects in flexible electronics, electronic equipment thermal management, and biomedical fields. However, liquid metal always maintains a spherical shape, and its huge surface tension makes it difficult to pattern it on the substrate for the preparation of flexible circuits, and its compatibility with the substrate is poor, making it difficult to evenly disperse it in the polymer matrix, which seriously limits the application of gallium-based liquid metal.

[0003] At present, the above problems are often solved by etching microchannels on the substrate to encapsulate liquid metal, or directly preparing large pieces of liquid metal into liquid metal microspheres by physical methods. Compared with etching microchannels, the method of preparing liquid metal microspheres by ultrasound or homogenization is simpler and the prepared liquid metal microspheres are relatively stable. However, although a thin layer of gallium oxide (0.5-3nm) will form on the surface of the liquid metal microspheres during the ultrasound process, this is still not enough to make the liquid metal microspheres have reliable colloidal stability.

[0004] In recent years, ligand modification engineering based on gallium-based liquid metal has developed rapidly. Thiols are often used as surfactants to stabilize liquid metal emulsions. However, thiols usually have a pungent odor and poor biocompatibility, which seriously limits the application of liquid metal microspheres prepared with them as surfactants. Improving the stability of gallium-based liquid metal, reducing its surface tension, and enhancing its compatibility with the substrate are of great significance for expanding its application range. Summary of the invention

[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a liquid metal slurry; the second purpose of the present invention is to provide a method for preparing the liquid metal slurry; the third purpose of the present invention is to provide an alloy ink; the fourth purpose of the present invention is to provide a Janus membrane; the fifth purpose of the present invention is to provide the application of the liquid metal slurry, alloy ink, or Janus membrane.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A first aspect of the present invention provides a liquid metal slurry, wherein the liquid metal slurry comprises a liquid metal Pickering emulsion; the liquid metal Pickering emulsion comprises liquid metal and a stabilizer;

[0008] The liquid metal includes gallium-based liquid metal;

[0009] The stabilizer includes cellulose nanocrystals.

[0010] Specifically, Pickering emulsion is an emulsion stabilized by solid particles. The solid particles, which are Pickering emulsifiers, have wettability to both water and oil phases and can be adsorbed on the oil-water interface to form a Pickering emulsion. Compared with emulsions stabilized by traditional surfactants, Pickering emulsions have the advantages of sustainability, greater stability, biocompatibility, and biodegradability. Cellulose nanocrystals are a one-dimensional rod-shaped nanomaterial that is mainly derived from wood and cotton. They have excellent biocompatibility and mechanical properties, a large aspect ratio, and are biodegradable. The surface of cellulose nanocrystals has abundant functional groups (hydroxyl groups, sulfonic acid groups), has good Pickering emulsification properties, and is an excellent emulsifier for stabilizing liquid metal Pickering emulsions.

[0011] Preferably, the gallium-based liquid metal includes at least one of a gallium-indium alloy, a gallium-tin alloy, and a gallium-indium-tin alloy.

[0012] Preferably, the content of metallic gallium in the gallium-based liquid metal is 70-85 wt %; further preferably, the content of metallic gallium in the gallium-based liquid metal is 75-80 wt %.

[0013] Preferably, the melting point of the gallium-based liquid metal is 16-30°C.

[0014] Preferably, the liquid metal slurry comprises the following preparation raw materials: liquid metal, stabilizer and water.

[0015] The second aspect of the present invention provides a method for preparing the liquid metal slurry according to the first aspect of the present invention, comprising the following steps:

[0016] The stabilizer is mixed with water to form a dispersion, and liquid metal is added to obtain the liquid metal slurry.

[0017] Preferably, the concentration of the dispersion is 5-15 mg / mL; more preferably, the concentration of the dispersion is 5-12 mg / mL.

[0018] Preferably, the mass ratio of the liquid metal to the dispersion is 1:(5-30); further preferably, the mass ratio of the liquid metal to the dispersion is 1:(8-25).

[0019] Preferably, the process of mixing the stabilizer with water is assisted by ultrasound.

[0020] Preferably, the power of the ultrasound is 150-350W; further preferably, the power of the ultrasound is 200-300W.

[0021] Preferably, the ultrasonic time is 5-10 min; more preferably, the ultrasonic time is 6-8 min.

[0022] Preferably, the process of mixing the liquid metal and the dispersion is assisted by ultrasound.

[0023] Preferably, the power of the ultrasound is 200-350W; further preferably, the power of the ultrasound is 240-300W.

[0024] Preferably, the ultrasonic time is 10-15 min; further preferably, the ultrasonic time is 10-12 min.

[0025] Preferably, the process of mixing the liquid metal with the dispersion is carried out in an ice bath.

[0026] The third aspect of the present invention provides an alloy ink, comprising the liquid metal slurry described in the first aspect of the present invention; the liquid metal slurry is subjected to centrifugal purification treatment.

[0027] Preferably, the centrifugal speed of the centrifugal purification treatment is 4000-7000 rpm; further preferably, the centrifugal speed of the centrifugal purification treatment is 5000-6000 rpm.

[0028] Preferably, the time for the centrifugal purification treatment is 5-10 min; further preferably, the time for the centrifugal purification treatment is 5-8 min.

[0029] The fourth aspect of the present invention provides a Janus membrane, comprising the liquid metal slurry described in the first aspect of the present invention, and a polymer matrix.

[0030] Preferably, the polymer matrix comprises waterborne polyurethane (WPU).

[0031] Preferably, the solid content mass ratio of the liquid metal slurry to the polymer matrix is ​​1:(1-3); further preferably, the solid content mass ratio of the liquid metal slurry to the polymer matrix is ​​1:(1-2).

[0032] Preferably, the Janus membrane is prepared by a method comprising the following steps:

[0033] The liquid metal slurry is mixed with the polymer matrix, and degassed and dried to obtain the Janus membrane.

[0034] Preferably, the process of mixing the liquid metal slurry and the polymer matrix is ​​firstly assisted by stirring and then subjected to water bath ultrasound.

[0035] Preferably, the stirring speed is 200-500 rpm; further preferably, the stirring speed is 300-400 rpm.

[0036] Preferably, the stirring time is 1-3 h; more preferably, the stirring time is 1-2 h.

[0037] Preferably, the water bath ultrasound time is 5-10 min; further preferably, the water bath ultrasound time is 6-8 min.

[0038] Preferably, the degassing is performed in a vacuum drying oven.

[0039] Preferably, the degassing conditions are: 20-25°C, and maintaining the temperature for 5-8 minutes after vacuuming.

[0040] Preferably, the drying temperature is 20-30°C; more preferably, the drying temperature is 25-30°C.

[0041] Preferably, the drying time is 3-5 days; further preferably, the drying time is 3-4 days.

[0042] The fifth aspect of the present invention provides the application of the liquid metal slurry described in the first aspect of the present invention, the alloy ink described in the third aspect, or the Janus film described in the fourth aspect in the field of flexible electronics.

[0043] Preferably, the flexible electronics are smart wearables.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] 1) The liquid metal slurry provided by the present invention has no obvious sedimentation and agglomeration phenomenon after standing for 24 hours, has good stability, and has the characteristics of Pickering emulsion. The emulsion microspheres in the liquid metal slurry are micron-sized, the spheres are uniform, and the dispersibility is good;

[0046] 2) The method for preparing the liquid metal slurry provided by the present invention has simple steps and mild process conditions;

[0047] 3) The alloy ink provided by the present invention can be obtained by centrifugation purification of liquid metal slurry. The alloy ink can be easily patterned on a substrate, has good adhesion to the substrate, and has low ink resistance, and has the potential to be applied to flexible electronics;

[0048] 4) The Janus membrane provided by the present invention has asymmetric morphological structures and chemical compositions on the upper and lower surfaces, the liquid metal emulsion microspheres are evenly distributed inside the membrane, and the liquid metal has good compatibility with the polymer matrix; the Janus membrane has good Joule thermal performance, photothermal conversion performance, good softness and elasticity, and has a resistance change response within a large strain range, which can meet the application requirements in the field of flexible electronics. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 The stability test results of the liquid metal slurry in Example 1;

[0050] Figure 2 is a SEM image of the liquid metal slurry in Example 1;

[0051] Figure 3 The pattern drawn using the alloy ink in Example 4;

[0052] Figure 4 Optical photographs of the upper surface (a) and lower surface (b) of the Janus film in Example 5;

[0053] Figure 5 SEM images of the upper surface (a) and lower surface (b) of the Janus membrane in Example 5;

[0054] Figure 6 is a SEM image of the cross section of the Janus membrane in Example 5;

[0055] Figure 7 is the conductivity of the Janus film after different strain stretching activation in Example 5;

[0056] Figure 8 is the Joule heat performance of the Janus film after stretching and activation in Example 5;

[0057] Fig. 9 The light-to-heat conversion effect of the Janus film after stretching and activation in Example 5;

[0058] Fig.10 is the stress-strain curve of the Janus membrane after stretching activation in Example 5;

[0059] Fig.11 This is the strain-resistance sensing performance test of the lower surface of the Janus film after stretching and activation in Example 5. DETAILED DESCRIPTION

[0060] The present invention is further described in detail below by specific examples. The raw materials, reagents or devices used in the examples can be obtained from conventional commercial sources or by prior art methods unless otherwise specified. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0061] Example 1

[0062] This embodiment provides a liquid metal slurry, which is prepared by the following steps:

[0063] 1) 0.2 g of cellulose nanocrystal powder was mixed with 39.8 g of deionized water, and ultrasonically dispersed at 200 W for 6 min to obtain a cellulose nanocrystal aqueous dispersion;

[0064] 2) 0.2 g of gallium-indium alloy liquid metal (gallium content of 75 wt %, melting point of 19° C.) was mixed with 4 g of cellulose nanocrystal aqueous dispersion, and ultrasonically treated at 240 W for 10 min in an ice-water bath to obtain a liquid metal slurry.

[0065] Example 2

[0066] This embodiment provides a liquid metal slurry, which is prepared by the following steps:

[0067] 1) 0.5 g of cellulose nanocrystal powder was mixed with 39.8 g of deionized water, and ultrasonically dispersed at 200 W for 6 min to obtain a cellulose nanocrystal aqueous dispersion;

[0068] 2) 0.5 g of gallium-tin alloy liquid metal (gallium content of 80 wt %, melting point of 16° C.) was mixed with 5 g of cellulose nanocrystal aqueous dispersion, and ultrasonically treated at 240 W for 10 min in an ice-water bath to obtain a liquid metal slurry.

[0069] Example 3

[0070] This embodiment provides a liquid metal slurry, which is prepared by the following steps:

[0071] 1) Mix 0.4 g of cellulose nanocrystal powder with 50 g of deionized water, and disperse them ultrasonically at 200 W for 6 min to obtain a cellulose nanocrystal aqueous dispersion;

[0072] 2) 0.4 g of gallium-indium-tin alloy liquid metal (gallium content of 75 wt %, melting point of 30° C.) was mixed with 8 g of cellulose nanocrystal aqueous dispersion, and ultrasonically treated at 240 W for 10 min in an ice-water bath to obtain a liquid metal slurry.

[0073] Example 4

[0074] This embodiment provides an alloy ink, which is prepared by the following steps:

[0075] The liquid metal slurry in Example 1 was centrifuged and purified at a speed of 5500 rpm for 6 min, and the supernatant was removed to obtain alloy ink.

[0076] Example 5

[0077] This embodiment provides a Janus membrane, which is prepared by the following steps:

[0078] Take the liquid metal slurry in Example 1, mix it with the aqueous polyurethane emulsion at a solid content mass ratio of 1:1, first stir it at a speed of 400 rpm for 2 hours, and then water bath sonicate it for 8 minutes; pour the emulsion after water bath sonication into a polytetrafluoroethylene mold, vacuum degas it in a vacuum drying oven at 25°C for 8 minutes, and then naturally dry it at room temperature 25°C for 3 days to obtain a Janus membrane.

[0079] Material Characterization and Performance Testing

[0080] 1. Stability test of liquid metal slurry in Example 1:

[0081] The liquid metal slurry in Example 1 was allowed to stand, and the sedimentation and agglomeration of the liquid metal slurry were observed at 0 min, 5 min, 6 h and 24 h.

[0082] Figure 1 The stability test results of the liquid metal slurry in Example 1 are shown from left to right, respectively, in the optical photographs of the liquid metal slurry after being left for 0 min, 5 min, 6 h, and 24 h. Figure 1 It can be seen that the liquid metal slurry in Example 1 remains stable after standing for 24 hours, with no obvious sedimentation and agglomeration phenomenon, indicating that in the liquid metal slurry provided by the present invention, the cellulose nanocrystals have a good emulsifying effect on the liquid metal, so that the liquid metal slurry has the characteristics of good Pickering emulsion stability.

[0083] 2. Observation of the morphology of the liquid metal slurry in Example 1:

[0084] The morphology of the liquid metal slurry in Example 1 was observed using a scanning electron microscope.

[0085] Figure 2 is a SEM image of the liquid metal slurry in Example 1. Figure 2 It can be seen that the emulsion size of the liquid metal slurry is in the micron level, the spheres of the emulsion microspheres are uniform, and the overall dispersion is good.

[0086] 3. Performance test of alloy ink in Example 4:

[0087] The alloy ink in Example 4 was loaded into a pen, a drawing was made on ordinary A4 paper, and the resistance of the ink writing was measured using a multimeter.

[0088] Figure 3 The pattern drawn using the alloy ink in Example 4 is Figure 3 It can be seen that the alloy ink obtained by centrifugal purification of the liquid metal slurry can be easily patterned on ordinary A4 paper, indicating that the liquid metal microspheres modified with cellulose nanocrystals provided in Example 1 have good adhesion to the substrate. The ink writing after mechanical activation has a resistance of 40-80Ω, which is relatively low, making it potentially applicable to flexible electronics.

[0089] 4. Morphological characterization of the Janus membrane in Example 5:

[0090] The upper and lower surfaces of the Janus film in Example 5 were observed, and the upper and lower surfaces, as well as the cross section of the Janus film were characterized using a scanning electron microscope.

[0091] Figure 4 The optical photographs of the upper surface (a) and the lower surface (b) of the Janus film in Example 5 are shown in FIG. Figure 4 It can be seen that the upper surface of the Janus membrane prepared in Example 5 is black, and the lower surface is silvery white.

[0092] Figure 5 The SEM images of the upper surface (a) and lower surface (b) of the Janus membrane in Example 5 are shown in FIG. Figure 5 It can be seen that the liquid metal emulsion microspheres are evenly distributed inside the membrane, indicating that the cellulose nanocrystals have a good dispersing effect on the liquid metal, making it evenly dispersed in the polymer matrix.

[0093] Figure 6 is a SEM image of the cross section of the Janus membrane in Example 5, Figure 6 It can be seen that the liquid metal emulsion microspheres are mainly distributed at the bottom of the membrane, and the particle size distribution gradually increases from top to bottom. Due to the presence of cellulose nanocrystals on the surface of the liquid metal emulsion microspheres and the certain spatial distance between them, no conductive path is formed between them. To form a conductive path, mechanical activation is required.

[0094] 5. Mechanical activation and conductivity test of Janus membrane:

[0095] The Janus membrane in Example 5 was stretched and activated five times with different strains less than or equal to 300, and the initial conductivity of the Janus membrane and the conductivity after each stretching and activation were measured.

[0096] Figure 7 is the conductivity of the Janus film after different strain stretching activation in Example 5, Figure 7 It can be seen that with the increase of tensile strain, the conductivity of the Janus film gradually increases until it becomes stable.

[0097] 6. Joule heat performance test of Janus film after stretching activation:

[0098] The surface temperature of the Janus film after stretching and activation was tested under an applied voltage of 5V. Figure 8 is the Joule thermal performance of the Janus film after stretching and activation in Example 5, Figure 8 It can be seen that the surface temperature of the Janus film after stretching activation is about 115°C under an applied voltage of 5V, and the surface temperature is proportional to the square of the applied voltage, which conforms to the Joule's heat law, indicating that the Janus film provided by the present invention has good Joule heat performance.

[0099] 7. Test of the photothermal conversion effect of the Janus film after stretching and activation:

[0100] The stretched and activated Janus film was irradiated with near-infrared light of 100 mW. Fig. 9 The light-to-heat conversion effect of the Janus film after stretching and activation in Example 5 is shown in FIG. Fig. 9 It can be seen that within 0-10s, the surface temperature of the Janus film after stretching activation rapidly increased from 15°C to nearly 120°C, and then within 50s, the temperature remained basically unchanged, indicating that the Janus film provided by the present invention has excellent light-to-heat conversion effect.

[0101] 8. Yield strength test of Janus membrane after tensile activation:

[0102] Fig.10 is the stress-strain curve of the Janus membrane after stretching activation in Example 5, Fig.10 It can be seen that the maximum stress that the Janus membrane can withstand is about 15 MPa, and the elongation at break can reach 533%, indicating that the Janus membrane provided by the present invention has good softness and elasticity.

[0103] 9. Strain-resistance sensing performance test of the lower surface of the Janus film after stretching activation:

[0104] Fig.11 The strain-resistance sensing performance test of the lower surface of the Janus film after stretching and activation in Example 5 is as follows: Fig.11 It can be seen that the Janus film has a resistance change response within a large strain range, indicating that it has the potential to be used in flexible electronics.

[0105] The liquid metal slurry provided by the present invention has good stability and good compatibility with the substrate. After forming an alloy ink, it can be easily patterned on the substrate and has low resistance characteristics. The Janus film prepared with the liquid metal slurry as the raw material has asymmetric morphology and chemical composition on both sides of the film, and the liquid metal emulsion microspheres have good dispersion in the polymer base. The mechanically activated Janus film has good Joule heat performance and photothermal conversion performance, good softness and elasticity, and has a resistance change response within a large strain range, which can meet the application requirements in the field of flexible electronics.

Claims

1. A liquid metal slurry, characterized in that: The liquid metal slurry comprises a liquid metal Pickering emulsion; the liquid metal Pickering emulsion comprises liquid metal and a stabilizer; The liquid metal includes gallium-based liquid metal; The stabilizer includes cellulose nanocrystals.

2. The liquid metal slurry according to claim 1, characterized in that: The gallium-based liquid metal includes at least one of a gallium-indium alloy, a gallium-tin alloy, and a gallium-indium-tin alloy; Preferably, the gallium content of the gallium-based liquid metal is 70-85 wt %; Preferably, the melting point of the gallium-based liquid metal is 16-30°C.

3. The liquid metal slurry according to claim 1 or 2, characterized in that: The liquid metal slurry comprises the following preparation raw materials: liquid metal, stabilizer and water.

4. The method for preparing the liquid metal slurry according to claim 3, characterized in that: The following steps are involved: The stabilizer is mixed with water to form a dispersion, and liquid metal is added to obtain the liquid metal slurry.

5. The preparation method according to claim 4, characterized in that: The concentration of the dispersion is 5-15 mg / mL; And / or, the mass ratio of the liquid metal to the dispersion is 1:(5-30).

6. An alloy ink, characterized in that: A liquid metal slurry comprising any one of claims 1 to 3; The liquid metal slurry is subjected to centrifugal purification treatment.

7. A Janus membrane, characterized in that: The invention comprises the liquid metal slurry as described in any one of claims 1 to 3, and a polymer matrix.

8. The Janus membrane according to claim 7, characterized in that The polymer matrix includes waterborne polyurethane; Preferably, the solid content mass ratio of the liquid metal slurry to the polymer matrix is ​​1:(1-3).

9. The Janus membrane according to claim 8, characterized in that The Janus membrane is prepared by a method comprising the following steps: The liquid metal slurry is mixed with the polymer matrix, and degassed and dried to obtain the Janus membrane.

10. Use of the liquid metal slurry according to any one of claims 1 to 3, the alloy ink according to claim 6, or the Janus film according to any one of claims 7 to 9 in the field of flexible electronics.

Citation Information

Cited By

  • Liquid metal enhanced triboelectric material with bionic surface and preparation method of liquid metal enhanced triboelectric material

    CN120966229A

  • Liquid metal reinforced triboelectric material with biomimetic surface and preparation method thereof

    CN120966229B